2018
DOI: 10.1177/0194599818778277
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes in Medical Therapy vs Surgical Intervention of Esophageal Foreign Bodies

Abstract: Objectives (1) Compare efficacy of primary medical therapy vs primary surgical intervention in patients with esophageal foreign bodies (EFBs). (2) Investigate variables that may predict successful outcomes in patients treated for EFBs. Study Design Case series with chart review. Setting Single-institution academic tertiary care medical center. Subjects and Methods Adult patients (older than 18 years) seen at the University of Michigan Emergency Department (ED) over an 8-year period with the diagnosis of EFBs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Given these findings, endoscopic intervention may be a preferred treatment. A recent study compared medical therapy versus endoscopic intervention and concluded first‐line endoscopic intervention was superior to medical therapy and should not be delayed for a trial of medical therapy due to concerns of higher morbidity with endoscopic intervention …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given these findings, endoscopic intervention may be a preferred treatment. A recent study compared medical therapy versus endoscopic intervention and concluded first‐line endoscopic intervention was superior to medical therapy and should not be delayed for a trial of medical therapy due to concerns of higher morbidity with endoscopic intervention …”
Section: Discussionmentioning
confidence: 99%
“…This is important because vomiting may increase the risk of aspiration and possibly esophageal perforation, and the latter is known to adversely affect morbidity from esophageal obstructions . One study reported the management of adverse events from glucagon included the need for fluid resuscitation secondary to hypotension and antiemetic administration . Additionally, two patients experienced lightheadedness or near syncope but did not require medical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Rigid esophagoscopy under general anesthesia has traditionally been used by otolaryngologists as the first-line treatment. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Other centers with different demographics report significantly lower rates of operative intervention. 7 From a clinical perspective, it would also be beneficial to know whether a given patient had ingested multiple objects at the same time, and this information is unfortunately not available in the National Electronic Injury Surveillance System. Dalal et al 8 evaluated their experience with 30 incarcerated patients who had 141 episodes of intentional ingestion; on average, 4.6 items were ingested per episode.…”
mentioning
confidence: 99%